1988
DOI: 10.1161/01.hyp.12.3.251
|View full text |Cite
|
Sign up to set email alerts
|

Influence of race, sex, and blood pressure on erythrocyte sodium transport in humans.

Abstract: SUMMARY Sodium transport of erythrocytes from normotensive and essential hypertensive subjects was evaluated by determining ouabain-sensitive and ouabain-insensitlve sodium efflux rates, Na + -LI + countertransport rates, Li + -K + cotransport rate constants flithium replacing sodium), intracellular sodium concentrations, and the number of Na + ,K + -adeoosine triphosphatase (ATPase) sites per erythrocyte. Subjects included men and women, blacks and whites. Hypertensive subjects had significantly higher sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 43 publications
(28 reference statements)
1
9
0
Order By: Relevance
“…When we restricted our analysis to Caucasian subjects, similar relationships were seen between AER and blood pressure (but not SLC) as in the whole group. The observation that Afro-Caribbean subjects had lower SLC than Caucasian subjects, confirms a finding previous, ly noted by other groups [21,22].…”
Section: Discussionsupporting
confidence: 89%
“…When we restricted our analysis to Caucasian subjects, similar relationships were seen between AER and blood pressure (but not SLC) as in the whole group. The observation that Afro-Caribbean subjects had lower SLC than Caucasian subjects, confirms a finding previous, ly noted by other groups [21,22].…”
Section: Discussionsupporting
confidence: 89%
“…Because RBC Na + content is directly related to passive membrane cation permeability and inversely related to activity of the Na + -K + pump, 23 it is possible that the fall in RBC Na + content we observed is the result of an alteration in either or both parameters. Previous in vitro studies clearly demonstrate that RBC membrane cholesterol enrichment decreases both passive cation leak permeability 22 and Na + , K + -ATPase activity, 24 and membrane cholesterol depletion stimulates Na + -K + pump activity.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, black women have the highest prevalence of hypertension. 26 In a recent report, Smith et al 27 reported that the black female hypertensive population was distinctive in their values for several of the Na + ,K + -ATPase pump parameters. This group had higher sodium pump sites per erythrocytes compared with other black groups.…”
mentioning
confidence: 99%
“…This subgroup also displayed the highest salt sensitivity of blood pressure compared with all other hypertensive groups. 28 Smith et al 27 did not measure the affinity constant for ouabain binding to erythrocytes. Hypertension is a multifactorial disease, and we do not know if our finding of decreased ouabain affinity of the enzyme is one of the risk factors that predispose these children to essential hypertension in adulthood, but our biochemical data are in excellent agreement with the epidemiological data.…”
mentioning
confidence: 99%